Горе от ума: [комедия] / А. С. Грибоедов - Грибоедов Александр Сергеевич (Библиотека школьника, 2012)
Экземпляры: ф.4 (20151209) / Инвентарный номер: 059861 / Цена: 56.00 / Авт.знак: Г 82 / ГРНТИ: 17.82.20 / ББК: 84(2Рос=Рус)1